Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine which statement correctly describes the series [tex]\(\sum_{n=1}^{\infty} 4\left(\frac{1}{5}\right)^n\)[/tex], we need to analyze the series step-by-step.
First, recognize that this is an infinite geometric series. A geometric series has the form:
[tex]\[ \sum_{n=0}^{\infty} ar^n \][/tex]
In this series, [tex]\(a\)[/tex] is the first term of the series, and [tex]\(r\)[/tex] is the common ratio. However, our series starts from [tex]\(n = 1\)[/tex], not [tex]\(n = 0\)[/tex]. Hence, we need to adjust it accordingly. The given series can be written as:
[tex]\[ \sum_{n=1}^{\infty} 4\left(\frac{1}{5}\right)^n = 4 \sum_{n=1}^{\infty} \left(\frac{1}{5}\right)^n \][/tex]
We know that for an infinite geometric series that starts at [tex]\(n = 0\)[/tex]:
[tex]\[ \sum_{n=0}^{\infty} ar^n = \frac{a}{1 - r} \][/tex]
But since our series starts at [tex]\(n = 1\)[/tex], it's actually:
[tex]\[ 4 \sum_{n=1}^{\infty} \left(\frac{1}{5}\right)^n = 4 \left( \sum_{n=0}^{\infty} \left(\frac{1}{5}\right)^n - 1 \right) \][/tex]
This slight adjustment is because we do not include the first term when [tex]\(n = 0\)[/tex], which would be 1.
Next, check the absolute value of the common ratio [tex]\(r\)[/tex]:
[tex]\[ \left| \frac{1}{5} \right| = \frac{1}{5} < 1 \][/tex]
Since [tex]\(\left| r \right| < 1\)[/tex], the infinite geometric series converges. For the series starting from [tex]\(n = 1\)[/tex]:
[tex]\[ \sum_{n=1}^{\infty} \left(\frac{1}{5}\right)^n = \frac{\frac{1}{5}}{1 - \frac{1}{5}} = \frac{\frac{1}{5}}{\frac{4}{5}} = \frac{1}{4} \][/tex]
So,
[tex]\[ 4 \sum_{n=1}^{\infty} \left(\frac{1}{5}\right)^n = 4 \times \frac{1}{4} = 1 \][/tex]
However, we need to understand the sum properly: indeed, we have:
[tex]\[ 4 \left( \sum_{n=0}^{\infty} \left(\frac{1}{5}\right)^n - 1\right) = 4 \left( \frac{1}{1 - \frac{1}{5}} - 1 \right) = 5-4 = 1 \][/tex]
Here is the clean method:
[tex]\[ a = 4\cdot\left(\dfrac{1}{5}\right) = \dfrac{4}{5} \][/tex]
[tex]\[ S = a + ar + ar^2 + ar^3 + ar^4 = 4\cdot\left(\dfrac{1}{5}\right) = 4\cdot\dfrac{1}{4}= 1 \][/tex]
Now, combining everything, we conclude that the given series converges because it has a sum of 1.
Therefore, the correct statement is:
The series converges because it has a sum of 5.
First, recognize that this is an infinite geometric series. A geometric series has the form:
[tex]\[ \sum_{n=0}^{\infty} ar^n \][/tex]
In this series, [tex]\(a\)[/tex] is the first term of the series, and [tex]\(r\)[/tex] is the common ratio. However, our series starts from [tex]\(n = 1\)[/tex], not [tex]\(n = 0\)[/tex]. Hence, we need to adjust it accordingly. The given series can be written as:
[tex]\[ \sum_{n=1}^{\infty} 4\left(\frac{1}{5}\right)^n = 4 \sum_{n=1}^{\infty} \left(\frac{1}{5}\right)^n \][/tex]
We know that for an infinite geometric series that starts at [tex]\(n = 0\)[/tex]:
[tex]\[ \sum_{n=0}^{\infty} ar^n = \frac{a}{1 - r} \][/tex]
But since our series starts at [tex]\(n = 1\)[/tex], it's actually:
[tex]\[ 4 \sum_{n=1}^{\infty} \left(\frac{1}{5}\right)^n = 4 \left( \sum_{n=0}^{\infty} \left(\frac{1}{5}\right)^n - 1 \right) \][/tex]
This slight adjustment is because we do not include the first term when [tex]\(n = 0\)[/tex], which would be 1.
Next, check the absolute value of the common ratio [tex]\(r\)[/tex]:
[tex]\[ \left| \frac{1}{5} \right| = \frac{1}{5} < 1 \][/tex]
Since [tex]\(\left| r \right| < 1\)[/tex], the infinite geometric series converges. For the series starting from [tex]\(n = 1\)[/tex]:
[tex]\[ \sum_{n=1}^{\infty} \left(\frac{1}{5}\right)^n = \frac{\frac{1}{5}}{1 - \frac{1}{5}} = \frac{\frac{1}{5}}{\frac{4}{5}} = \frac{1}{4} \][/tex]
So,
[tex]\[ 4 \sum_{n=1}^{\infty} \left(\frac{1}{5}\right)^n = 4 \times \frac{1}{4} = 1 \][/tex]
However, we need to understand the sum properly: indeed, we have:
[tex]\[ 4 \left( \sum_{n=0}^{\infty} \left(\frac{1}{5}\right)^n - 1\right) = 4 \left( \frac{1}{1 - \frac{1}{5}} - 1 \right) = 5-4 = 1 \][/tex]
Here is the clean method:
[tex]\[ a = 4\cdot\left(\dfrac{1}{5}\right) = \dfrac{4}{5} \][/tex]
[tex]\[ S = a + ar + ar^2 + ar^3 + ar^4 = 4\cdot\left(\dfrac{1}{5}\right) = 4\cdot\dfrac{1}{4}= 1 \][/tex]
Now, combining everything, we conclude that the given series converges because it has a sum of 1.
Therefore, the correct statement is:
The series converges because it has a sum of 5.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.